Development of Quality Protein Maize based breakfast cereal - PRAKASH, OM; JHA, S K; RUDRA, S G; JHA, G K; SINHA, J P; HOSSAIN, FIROZ (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out at ICAR-IARI, New Delhi during 2012-16 to evaluate the effect of extrusion parameters namely, barrel temperature (100-140°C), screw speed (300-500 rpm) and feed moisture addition (6-18% wb) on quality of QPM (Var. HQPM1) based expanded extruded product. The optimum extrusion processing condition (9.75% feed moisture addition, 125°C temperature and 461 rpm screw speed) was established for QPM. At this extrusion condition, the effect of addition of finger millet and carrot powder on quality of QPM based extruded product was determined. Addition of up to 20% finger millet was found optimum for retaining acceptable colour in the extrudate. Addition of carrot powder to QPM-finger millet base imparted reddish colour to the extruded product and also led to decrease in expansion ratio and increase in bulk density. Colour (â€œa-valueâ€) increased with increase in carrot powder in the sample, indicating increase in redness of the product. Based on physical appearance of the sample, as well as expansion ratio and a-value, addition of 10% carrot powder was considered optimum. A breakfast cereal was thus developed through extrusion processing at optimum conditions using ingredients composition of 72% maize (QPM and normal maize), 18% finger millet and 10% carrot powder. The final product obtained had 9.6% protein, 1.5% fat, 3.4% fibre, 2 mg/100g Î²-carotene, 3 mg/100g iron and 122 mg/100g calcium. Amino acids (especially tryptophan and lysine) were higher in quality protein maize based product than normal maize based product.